Legal aspects of noise prevention in rural areas - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2018)
The aim of the deliberations presented was an attempt to assess the legal system of the regulation concerning the protection of the environment against noise in rural areas, and to answer the question to what extent the current legislation takes into account the specificity of noise threats occurring in rural areas and whether it provides for an effective and adequate system of instruments for the protection of the acoustic climate of the rural environment. In the conclusion the author states that the specificity of noise prevention in rural areas has been adequately taken into account, despite a clear focus of the regulation put on noise in urban areas. However, the potential of taking a qualitative approach to noise prevention in rural areas or implementing legal instruments for the protection of areas with good acoustic climate, e.g. quiet areas, still remains unexploited, and noise intervention measures continue to be insufficiently included in spatial planning.